1984
DOI: 10.1099/00222615-17-3-317
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical fingerprinting of Clostridium difficile strains isolated from an outbreak of antibiotic-associated colitis and diarrhoea

Abstract: SUMMARY. Twenty eight strains of Clostridium dificile, isolated from an outbreak of antibiotic-associated colitis and diarrhoea in an orthopaedic ward and from sporadic cases throughout Sweden, were sent to Edinburgh for immunochemical fingerprinting without information about their origin. EDTA extracts of the organisms were examined by crossed immunoelectrophoresis (CIE), polyacrylamide gel electrophoresis (PAGE) and electroblot transfer. Two patterns were revealed by CIE: group A (18 strains) and group B (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…To type our strains, a simple and straightforward method, originally described by Poxton et al, [12] i.e., the electrophoretic patterns of whole-cell and excretory proteins from strains grown under standardized conditions, was used. By this method, a great variety of patterns was obtained from the strains examined.…”
Section: Resultsmentioning
confidence: 99%
“…To type our strains, a simple and straightforward method, originally described by Poxton et al, [12] i.e., the electrophoretic patterns of whole-cell and excretory proteins from strains grown under standardized conditions, was used. By this method, a great variety of patterns was obtained from the strains examined.…”
Section: Resultsmentioning
confidence: 99%
“…The immediate environment of infected patients has been found by a number of workers [41,42] to be contaminated with C. difficile, and in some studies, typing has confirmed that environmental isolates are often of the same type as those of the infected patient with which they are associated [14,28]. The Manchester environmental samples included two samples from bed linen and the floor associated with one patient, plus a cubicle curtain sample from a second patient; all were of the same EP type as the patient isolates themselves, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Differing electrophoretic methodologies have been employed in the typing of C. difficile by protein patterns and it appears to be the most popular general approach. These include radio-labelled [12,16], EDTA-extracted surface proteins [7,22], and whole-cell proteins [23][24][25] and, in addition, these may be coupled with immunoblotting techniques [26][27][28]. Discrimination is extremely high and in theory all strains can be typed; in practice, well over 95 % of isolates can be typed to previously defined types and any new patterns can be added as new types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main aims of this investigation were to determine the level of C. difficile colonization and disease in a population of elderly patients by routine culture and toxin detection methods, and to use a novel typing method based on the variation of the S-layer proteins from C. difficile to compare the strains in the patients and the ward environment. S-typing is a simplified modification of the method based on EDTA-soluble peptides, which was the first-ever method used to show that C. difficile was acquired exogenously (Poxton et al, 1984). The present study was part of a major prospective epidemiological study to investigate the use of inferential stochastic modelling to determine control methods for C. difficile disease -this is being submitted elsewhere.…”
Section: Introductionmentioning
confidence: 99%